Chemical coupling of thiolated chitosan to preformed liposomes improves mucoadhesive properties - Gradauer, Kerstin (Dove Medical Press, 2012)
AIM: To develop mucoadhesive liposomes by anchoring the polymer chitosan-thioglycolic acid (chitosan-TGA) to the liposomal surface to target intestinal mucosal membranes. METHODS: Liposomes consisting of phosphatidylcholine (POPC) and a maleimide-functionalized lipid were incubated with chitosan-TGA, leading to the formation of a thioether bond between free SH-groups of the polymer and maleimide groups of the liposome. Uncoated and newly generated thiomer-coated liposomes were characterized according to their size, zeta potential, and morphology using photon correlation spectroscopy and transmission electron microscopy. The release behavior of calcitonin and the fluorophore/quencher-couple ANTS/DPX (8-aminonaphthalene-1,3,6-trisulfonic acid/p-xylene-bis- pyridinium bromide) from coated and uncoated liposomes, was investigated over 24 hours in simulated gastric and intestinal fluids. To test the mucoadhesive properties of thiomer-coated and uncoated liposomes in-vitro, we used freshly excised porcine small intestine. RESULTS: Liposomes showed a concentration-dependent increase in size – from approximately 167 nm for uncoated liposomes to 439 nm for the highest thiomer concentration used in this study. Likewise, their zeta potentials gradually increased from about −38 mV to +20 mV, clearly indicating an effective coupling of chitosan-TGA to the surface of liposomes. As a result of mucoadhesion tests, we found an almost two-fold increase in the mucoadhesion of coupled liposomes relative to uncoupled ones. With fluorescence microscopy, we saw a tight adherence of coated particles to the intestinal mucus. CONCLUSION: Taken together, our current results indicate that thiomer-coated liposomes possess a high potential to be used as an oral drug-delivery system.